TAKSONOMI TRANSENDEN (PARADIGMA BARU TUJUAN PENDIDIKAN ISLAM) - Ah. Zakki Fuad (UIN Sunan Ampel Surabaya, 2014)
The Taxonomy of the Objectives of Islamic Education in the Qur'anic Perspective. This study is initiated from a thought that